Epidemiological Features of NAFLD From 1999 to 2018 in China - Zhou, Jianghua; Zhou, Feng; Wang, Wenxin; Zhang, Xiao‐Jing; Ji, Yan‐Xiao; Zhang, Peng; She, Zhi‐Gang; Zhu, Lihua; Cai, Jingjing; Li, Hongliang (Hepatology (Baltimore, Md.), 2020)
With dramatic changes in lifestyles over the last 20 years, nonalcoholic fatty liver disease (NAFLD) has become the most prevalent liver disorder in China but has not received sufficient attention. NAFLD‐related advanced liver disease and its mortality along with its overall disease burden are expected to increase substantially. There is thus an imperative need to clarify the epidemiological features of NAFLD to guide a holistic approach to management. We summarize eight epidemiological features of NAFLD in China over the past two decades using systematic review and meta‐analysis methodology. Our data reveal a rapid growth in the NAFLD population, especially among younger individuals. Importantly, there is a strong ethnic difference in body mass index (BMI) and genetic risk of NAFLD compared with the US population. The etiology of advanced liver disease and its complications (e.g., hepatocellular carcinoma) has been altered because of a Westernized lifestyle and the implementation of effective vaccination strategies against viral hepatitis. Regional epidemiological patterns of NAFLD indicate that economics, environment, and lifestyle are critical factors in disease progression. The analysis also indicates that a large number of patients remain undiagnosed and untreated because of the inadequacy of diagnostic tools and the absence of effective pharmacologic therapies. Given the burden of NAFLD, future policy and research efforts need to address knowledge gaps to mitigate the risk burden.